Manipulation of biological cells under ESEM and microfluidic systems - Fukuda, T. (wiley, 2015)
Cell manipulation requires not only the ability to observe the cells but also the ability to probe the cells. This chapter focuses on the manipulation of biological samples inside two different platforms, that is, environmental scanning electron microscope (ESEM) and microfluidic device. One example of cell manipulation inside ESEM platform is presented, that is, the manipulation of cells using dual nanoprobe, and one example of cell manipulation inside microfluidic device is highlighted, that is, the manipulation of cells using thermoresponsive polymer actuated (TPA) probe. Unlike Atomic Force Microscope (AFM) system, ESEM-nanomanipulation system can provide both 2D and 3D manipulations on the sample, thus increasing the flexibility of the measurement. Poly(N-isopropylacrylamide) (PNIPAAm) solution saves energy when generating the soluble-insoluble transition. To realize the probe manipulation, the semiclosed microchip has the bath in the middle of microchannel.